Discrete element modeling of particle-based additive manufacturing processes - Steuben, John C.; Iliopoulos, Athanasios P.; Michopoulos, John G. (Computer methods in applied mechanics and engineering, 2016)
A critical element for the design, characterization, and certification of materials and products produced by additive manufacturing processes is the ability to accurately and efficiently model the associated materials and processes. This is necessary for tailoring these processes to endow the associated products with proper geometrical and functional features. In an effort to address these needs in a computationally elegant and at the same time physically realistic manner, this paper presents the development of a methodology for simulating particle-based additive manufacturing processes, which employs the Discrete Element Method (DEM) extended to incorporate thermal physics. The details of the DEM-based methodology are presented first and the approach is demonstrated on a pair of test problems involving laser sintering of metal powders. The paper concludes with a discussion on how this approach may be generalized to broader classes of additive manufacturing systems, and details are given regarding future work necessary to further develop the present methodology.